Probiotic Fermentation and Organic Acid Profile in Milk Based Lactic Beverages Containing Potential Prebiotic Apple Constituents - Abdullah Barat; Melike Ciniviz; Gökçe Keser; Berrak Delikanlı Kıyak; Arzu Akpınar Bayizit; Lütfiye Yılmaz Ersan; Tülay Özcan (Journal of Agricultural Sciences)
Probiotic milk-based matrices contain bioactive compounds required for the biochemical and physiological processes of metabolism as a result of fermentation. The present work aimed to evaluate the viability of probiotic bacteria in a lactic beverage fortified with probiotic milk/apple juice to understand the utilization of apple juice as a prebiotic source and investigate the organic acid profile. By monitoring the fermentation development and bacterial growth the results obtained indicated that the probiotic bacteria were viable over the predicted shelf life; the cell counts ranged from 7.48 to 12.00 log10 cfu mL-1, conferring that the beneficial health effects on the host as probiotic bacteria must be at a minimum concentration of 6.0 log10 cfu mL-1 at the moment of consumption. Lactobacillus casei exhibited higher survival than the other lactic strains, presumably due to its higher ability to tolerate low acidity. During the fermentation and storage of milk based lactic beverages containing apple juice the formation of organic acids were determined as an indirect characteristic for growth of lactic acid bacteria. Lactic, acetic, malic, tartaric and citric acids were the primary organic acids. The quantities of propionic and butyric acids as short chain fatty acids were noted to increase during fermentation, being strain-specific. In conclusion, when probiotic milk is fortified with apple juice nutraceutical components, it can be a potential source of substrate and a synbiotic matrix for the growth of probiotic bacteria without any nutritional supplement.